Large‐scale population genetic structure in Bonelli's Eagle Aquila fasciata. (6th June 2013) - Mira, Sara; Arnaud‐Haond, Sophie; Palma, Luís; Cancela, Maria Leonor; Beja, Pedro; Fuchs, Jerome
<x xml:space="preserve">Abstract</x> In bird species that have a high movement capacity, dispersal may connect subpopulations over vast geographical regions, with important consequences for the design of conservation management strategies. Here we used a molecular approach to infer the patterns and rates of dispersal among eight Mediterranean subpopulations of the endangered Bonelli's Eagle, based on 245 individuals screened at 17 microsatellite loci. There was moderate genetic differentiation between subpopulations sampled in the western (Iberia and Morocco) and eastern (Cyprus) Mediterranean, whereas differentiation among subpopulations in the former region was weak to moderate and followed a pattern of isolation by distance. Within the western Mediterranean, the small, peripheral and ecologically unique population of southwest Portugal had the lowest genetic diversity and the highest differentiation. The remaining subpopulations formed two loose clusters, one including Morocco and southwest and eastern Spain, and the other northeast Portugal and western and central Spain. Few recent migrants were detected, and they originated primarily from adjacent subpopulations. Our findings suggest that western Mediterranean Bonelli's Eagles may have a large‐scale metapopulation structure, with subpopulations connected to some extent by distance‐dependent dispersal, probably influenced by natal philopatry and the geographical configuration of subpopulations. The combination of marked ecological and genetic divergence suggests that the peripheral subpopulation of southwest Portugal may be regarded as a distinct management unit.